Adjudicating at the Appellate Grade New Grounds in a Marriage Case "as if in first instance": Canon 1683 - Ingels, Gregory (CLSA advisory opinions, 2001-2005, 2001)
A marriage case receives a negative decision at first instance and is appealed by the petitioner. At second instance, the tribunal determines a new grounds for nullity, admits the case, judges it "as if in first instance," and finds in the affirmative. To which tribunal must this sentence now be transmitted for review?